The 2010 Meningococcal outbreak in Bahia, Brazil, was caused by 2 different STs belonging to Clonal Complex ST-103 / O surto de meningite meningocócica de 2010 na Bahia foi causado por dois ST diferentes pertencentes ao Complexo Clonal ST-103 - Ivano de Filippis; Rita de Cássia Vilasboas Silva; Márcia Falcão Modesto Ungar de Sá; Guilherme Gonçalves Sardinha; Soraia M.Cordeiro (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
An outbreak of meningococcal disease in the North-East (NE) region of Brazil with eleven cases and seven deaths was reported in 2009. From the eleven cases, ﬁ ve serogroup C meningococcal strains were isolated, four were classiﬁ ed as belonging to the hypervirulent clonal complex ST-103 (cc103) and one strain was not associated with any clonal complex. DNA sequencing of the genes encoding outer membrane proteins PorA and FetA showed genotype P1.5-1,10-1,36-2;F3-9 for all ﬁ ve strains. cc103 was ﬁ rst detected in the southern region of Brazil in 2007, but not associated with outbreaks. MLST analysis detected three new STs among the isolates, showing the ongoing evolution of cc103 and the need of monitoring its spread in the population. -------------------------------------------------------------------------- Um surto de doença meningocócica foi detectado em 2009 no estado da Bahia (NE) com onze casos conﬁrmados e sete óbitos. A partir do material coletado dos onze casos foi possível isolar cinco cepas de meningococos do sorogrupo C, sendo quatro pertencentes ao complexo clonal hipervirulento ST-103 (cc103), enquanto que uma cepa não foi associada a nenhum complexo clonal. O sequenciamento dos genes codiﬁcantes das proteínas de membrana PorA e FetA resultou no genótipo P1.5-1,10-1,36-2;F3-9 para todas as cepas. O cc103 foi isolado pela primeira vez na região sul do Brasil em 2007, mas não de um surto. A análise por MLST detectou a presença de três novos entre os isolados, o que mostra a contínua evolução do clone cc103 e a necessidade do monitoramento de seu avanço na população susceptível.